Organic Farming: An approach for sustainable agriculture - Singh, S P; Patel, Chanchala Rani (Indian Farming, 2022)
Organic farming provides quality food products and fibers which are beneficial to human health without adversely affecting soil health and environment. Organic farming is a way to keep the soil alive and in good health through the use of biological wastes and other biological materials along with beneficial microbes to release plant nutrients (macronutrients and micronutrients) to crops for increased sustainable production in an ecofriendly, pollution free environment. There is a need to identify suitable crops/ products on agro climatic zone basis as conventional farming is shifting its way towards organic farming. Some agro climatic zones have great potential for organic farming and many products can be produced organically. Trading is a major constraint in organic farming due to policy issues. Organic farming can provide ample opportunities for employment.